Training as Mediating in the Relationship Between Organization Reward and Employee Motivation - Muhammad Asif Khan; Asima Siddique; Zahid Sarwar (Journal of Business & Tourism, 2021)
Training and organization rewards plays important role in the development and motivation of the employees. And organization gives more attention to reward and training programs to motivate their employees. The purpose of this paper is to examine the relationship in between rewards and employees motivation. In addition the paper also aims to measure the mediating role of training.Employee’sidea and perception about organizational rewards and its impact on employee’s motivation have been evaluated empirically with the sample of 173 employees in district account offices. The data have been collected from the employees using survey method. SPSS have beenused to analyze the data the results show the mediating effect of training on the relationship between organization rewards and employee’s motivation. The results show that both training and organizational rewards have positive association with employee’s motivation.The study will help the administration of district account offices to develop policy that will cope with the challenges and difficulties in training and rewards management. And it will help in employee’s motivation.